5-HT2A receptor loss does not alter acute fluoxetine-induced anxiety and exhibit sex-dependent regulation of cortical immediate early gene expression. Issue 1 (1st February 2019) - Jaggar, Minal; Banerjee, Toshali; Weisstaub, Noelia; Gingrich, Jay A.; Vaidya, Vidita A.
Abstract: Background: Acute treatment with the selective serotonin reuptake inhibitor (SSRI), fluoxetine (Flx), induces anxiety-like behavioral effects. The serotonin2A receptor (5-HT2A ) is implicated in the modulation of anxiety-like behavior, however its contribution to the anxiogenic effects of acute Flx remains unclear. Here, we examined the role of the 5-HT2A receptor in the effects of acute Flx on anxiety-like behavior, serum corticosterone levels, neural activation and immediate early gene (IEG) expression in stress-responsive brain regions, using 5-HT2A receptor knockout (5-HT2A −/− ) mice of both sexes. Methods: 5-HT2A −/− and wild-type (WT) male and female mice received a single administration of Flx or vehicle, and were examined for anxiety-like behavior, serum corticosterone levels, FBJ murine osteosarcoma viral oncogene homolog peptide (c-Fos) positive cell numbers in stress-responsive brain regions of the hypothalamus and prefrontal cortex (PFC), and PFC IEG expression. Results: The increased anxiety-like behavior and enhanced corticosterone levels evoked by acute Flx were unaltered in 5-HT2A −/− mice of both sexes. 5-HT2A −/− female mice exhibited a diminished neural activation in the hypothalamus in response to acute Flx. Further, 5-HT2A −/− male, but not female, mice displayed altered baseline expression of several IEGs (brain-derived neurotrophic factor ( Bdnf ), Egr2, Egr4, FBJ osteosarcoma gene ( Fos ), FBJ murine osteosarcoma viral oncogene homolog B ( Fosb ), Fos-like antigen 2 ( Fosl2 ), Homer scaffolding protein ( Homer ) 1-3 ( Homer1-3 ), Jun proto-oncogene ( Jun )) in the PFC. Conclusion: Our results indicate that the increased anxiety and serum corticosterone levels evoked by acute Flx are not influenced by 5-HT2A receptor deficiency. However, the loss of function of the 5-HT2A receptor alters the degree of neural activation of the paraventricular nucleus (PVN) of the hypothalamus in response to acute Flx, and baseline expression of several IEGs in the PFC in a sexually dimorphic manner.